Influência da via hippo em carcinomas de células escamosas de língua oral - Torres, Ondina Karla Mousinho Rocha (2022)
Oral tongue squamous cell carcinoma (OTSCC) has high morbidity and mortality rates. Despite the progress made in this area, researchers continue to search for molecular biomarkers that have predictive value in the prognosis of patients and allow the development of new therapeutic strategies. In this context, several studies have highlighted the role of the Hippo pathway for this purpose. Therefore, this research aimed to evaluate whether the proteins related to the Hippo pathway, LATS2 and YAP1, have some influence on the OTSCC biological behavior. The sample consisted of 26 OTSCC cases and 8 normal oral mucosa cases as control. For the morphological assessment of OTSCC, the gradations proposed by the WHO (2005) and by Almangush et al. (2014) were performed. The immunohistochemical profile of LATS2 and YAP1 was evaluated by scores (0-3), based on their immunoexpression in intracellular location (nucleus and/or cytoplasm) and epithelial distribution. Pearson's Chi-square and Fisher's Exact statistical tests were performed for the analysis of the studied parameters. Survival analysis was performed using the Kaplan-Meier method and the log-rank test. For all evaluations, values with p<0.05 were considered significant. High expression of LATS2 was observed both in normal oral mucosa (100%) and in most OTSCC (73,1%), with no statistically significant difference (p=0,160). It was possible to observe the increase in YAP immunoexpression in cases of OTSCC compared to the normal oral mucosa (p<0.001). It was also found that the LATS2 low expression was associated with lower rates of disease-free survival (p=0.039). Furthermore, YAP high expression was found associated with the BD model's high-risk classification (p=0.034), suggesting this protein immunoexpression may be associated with EMT and cell invasion in OTSCC. The high expression of both proteins in most OTSCC suggests that other signaling pathways, in addition to regulating through LATS2, may be inducing the nuclear YAP expression in these tumors. Therefore, it is concluded that the Hippo pathway can influence the OTSCC biological behavior.